Chemical Kinetics and Reactive Species in Normal Saline Activated by a Surface Air Discharge. Issue 4 (5th October 2016) - Liu, Zhi Chao; Guo, Li; Liu, Ding Xin; Rong, Ming Zhe; Chen, Hai Lan; Kong, Michael G.
Abstract : Normal saline is a common biological solution which provides much better living environment for Staphylococcus aureus than deionized water, but the plasma‐activated normal saline is found to have a stronger bactericidal effect than the plasma‐activated deionized water. A model is developed for the explanation, from which various kinds of reactive chlorine/oxy‐chlorine species (RCS), such as HClO, are found to be generated in the plasma‐activated normal saline. The production pathways of RCS are elucidated, in which O3 plays as an important intermediate species. Compared to the plasma‐activated deionized water, the concentrations of reactive oxygen/nitrogen species are lower, but the bactericidal effect is higher, implying that the RCS play a crucial role for the sterilization. Abstract : Plasma‐activated normal saline is found to have a stronger bactericidal effect than the plasma‐activated deionized water, which may be attributed to the production of reactive chlorine/oxy‐chlorine species especially for HClO. A model is developed for the interaction between surface air plasmas and normal saline, from which the chemical profile of reactive chlorine/oxy‐chlorine species is provided.